El ciclo de biomasa en bosques de frondosas del sur de extremadura. variabilidad espacial del desfronde - TORRES, E; CUEVAS, S; VÁZQUEZ, F Ma; SUÁREZ, Ma A (II Congreso Forestal Español, 1997)
The knowledge of the biomass and nutrients cycle is very important for a suitable forest management. In this paper, four broadleaved species litterfall, during november 1996, is studied in Extremadura (Spain): Castanea sativa Miller, Quercus pyrenaica Willd, Q. rotundifolia Lam and Q. suber L. Litterfall is compared in sorne forests with different maturity. Also, orientation, position and individual tree factors influence is analysed
Keywords: Castanea sativa; Extremadura; litterfall; Quercus pyrenaica; Quercus rotundifolia; Quercus suber